2013
DOI: 10.2147/ijn.s39880
|View full text |Cite
|
Sign up to set email alerts
|

A concise review of magnetic resonance molecular imaging of tumor angiogenesis by targeting integrin αvβ3 with magnetic probes

Abstract: Angiogenesis is an essential step for the growth and spread of malignant tumors. Accurate detection and quantification of tumor angiogenesis is important for early diagnosis of cancers as well as post therapy assessment of antiangiogenic drugs. The cell adhesion molecule integrin αvβ3 is a specific marker of angiogenesis, which is highly expressed on activated and proliferating endothelial cells, but generally not on quiescent endothelial cells. Therefore, in recent years, many different approaches have been d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 71 publications
(71 reference statements)
0
5
0
Order By: Relevance
“…Significant effort has been expended exploring the clinical utility of imaging α V β 3 7 , 8 expression associated with tumor angiogenesis and metastatic dissemination 9 , 10 . For example, radiolabeled integrin peptide ligands with a pentapeptide motif Arg-Gly-Asp-Phe-Lys (RGDfK) have been used as tools in research aimed at developing radiotracers for clinical applications 11 , 12 . Numerous linear and cyclic RGD peptides based (to a greater or lesser extent) on the RGDfK motif, in combination with a variety of pharmacokinetic modifiers, prosthetic groups or bifunctional chelators and radionuclides have been reported and used as diagnostic probes in animal studies and clinical investigations in the areas of oncology 13 23 and cardiology 24 27 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significant effort has been expended exploring the clinical utility of imaging α V β 3 7 , 8 expression associated with tumor angiogenesis and metastatic dissemination 9 , 10 . For example, radiolabeled integrin peptide ligands with a pentapeptide motif Arg-Gly-Asp-Phe-Lys (RGDfK) have been used as tools in research aimed at developing radiotracers for clinical applications 11 , 12 . Numerous linear and cyclic RGD peptides based (to a greater or lesser extent) on the RGDfK motif, in combination with a variety of pharmacokinetic modifiers, prosthetic groups or bifunctional chelators and radionuclides have been reported and used as diagnostic probes in animal studies and clinical investigations in the areas of oncology 13 23 and cardiology 24 27 .…”
Section: Introductionmentioning
confidence: 99%
“…This led to the conclusion that the dimeric subclass of the RGD peptides is an optimal choice for the development of imaging agents for clinical applications 15 , 23 , 39 . The SPECT tracer 99 m Tc-3PRGD 2 34 , 40 – 43 as well as several RGD-based PET radiotracers 44 48 , have already entered clinical investigation stage 12 .…”
Section: Introductionmentioning
confidence: 99%
“…Without dynamic quantitative MR analyses, it is not possible to determine whether their characteristics translate into improved in vivo sensitivity and/or targeting compared to conventional agents. In terms of imaging glioma cells as opposed to angiography, 26 there are limited examples of molecular CAs that cross the blood brain barrier with a single Gd chelate. One promising example involves the use of an antibody to c-Met, the HGF receptor, linked to Gd-DTPA-albumin, reported to enhance a mouse model of glioma for up to 3 hours after administration.…”
Section: Resultsmentioning
confidence: 99%
“…The expression of αvβ3 integrin as a genuine marker of angiogenesis is only applicable to specific tumor types where its expression is restricted to vasculature; a key question in integrin imaging research is to what extent neovessel integrin expression contributes to radio-labeled imaging agents’ binding capacity. Some aspects of T7 and integrin αvβ3 receptor behavior have been explored, 9 , 10 , 18 but in the context of diagnostic imaging, agents remain relatively underexplored. In the current study, we directly assessed the relationship of binding kinetics between T7 and T7-6H, with an introduction 6 histidine into the C-terminus of the T7 peptide, and an analysis of αvβ3 density in the in vitro cell lines and in vivo animal models.…”
Section: Discussionmentioning
confidence: 99%
“… 5 7 A few researches also reveal that many ligands are able to bind to integrin αvβ3 in an RGD-independent way, such as SDV (Ser-Asp-Val) and SLV (Ser-Leu-Val). 8 , 9 In our previous studies, 10 we studied a peptide (T7) derived from tumstatin with the sequence of Thr-Met-Pro-Phe-Leu-Phe-Cys-Asn-Val-Asn-Asp-Val-Cys-Asn-Phe-Ala-Ser-Arg-Asn-Asp-Tyr-Ser-Tyr-Trp-Leu (TMPFLFCNVNDVCNFASRNDYSYWL), 11 14 the results indicated that the binding specificity between T7 peptide and integrin αvβ3 is located at the active sites of Ser90, Arg91, Asp93, and Tyr94, a new non-RGD-dependent binding mode, namely RNDY binding mode. Other studies showed that the critical amino acid sites for anti-angiogenesis in T7 peptide were Leu78, Val82, and Asp84.…”
Section: Introductionmentioning
confidence: 99%